Analisis Faktor-Faktor Konsumen Terhadap Purchase Intention Sepeda Listrik Menggunakan TAM3 - Maulia Regita Belananda; Muhammad Rezki Ian; Jamal Jamal (Owner : Riset dan Jurnal Akuntansi, 2025)
of people's strong purchasing power and the reasonable cost of electric bicycles. Purposive sampling was employed in questionnaire sampling. Because this study has forty indikator items, it requires a sample size of 200 respondents. The TAM3 model, which has 17 variables, is used in the research model. Only three variables—Subjective Norm, work relevance, and Output Quality—are known to be partially significant and to positively impact Perceived Usefulness . Five factors are identified as partially significant determinants of Perceived Ease of Use; three factors are positively correlated: Self-efficacy, Playfulness, and enjoyment; the other two are negatively correlated: Anxiety and Objective Usability. Perceived Usefulness  and Perceived Ease of Use are partially known to have a positive and significant influence on Behavioral Intention. Then it is known that Behavioral Intention has a positive and significant influence on Purchase Intention.